1999 : Victory Without War - Nixon, Richard (London Sidgwick and Jackson, 1988)
An analysis by Richard Nixon as commentator on world affairs, arguing that Soviet aims have not changed under Gorbachev, presenting his view of what future Western strategy should be. He also examines the future prospects of Western Europe, Japan, China and the Third World.
Include Index
Keywords: United States -- World politics -- Diplomatic relations